Oppressions in Popular Culture’s SpongeBob SquarePants Episode of “Drive Thru” - Suwandi, Kenny Christian; Dukut, Ekawati Marhaenny; Riyandari, Angelika (Soegijapranata Catholic University, 2021)
Abstract: This article is a development of the research done for an undergraduate study, which has the objectives to find the oppressions exercised by Mr. Krabs in USA’s “Drive Thru” episode of SpongeBob SquarePants cartoon TV series. Using Karl Marx’s theory in the study, it is revealed that the episode represents the oppressions by the Bourgeoisie capitalist towards the Proletariat. The data were discussed by using descriptive explanation and were analyzed and interpreted with the finding that the Bourgeoisie treated Proletariat rudely when it comes about money. As a development of the study, this article adds into the discussion on the explanation of Mr. Krabs actions based on the concept of Popular Culture’s strategies of making profit at the expense of the Proletariat.Key words: popular culture, cartoon, oppression, Marxism, profit makingAbstrak: Artikel ini merupakan pengembangan dari penelitian yang dilakukan sebagai bagian dari studi S1, yang bertujuan untuk untuk menemukan penindasan yang dilakukan oleh Tuan. Krabs pada episode “Drive Thru” dari serial kartun televisi SpongeBob SquarePants. Menggunakan teori Karl Marx terungkap bahwa episode tersebut merepresentasikan penindasan kaum kapitalis Borjuis terhadap kaum Proletar. Data yang ada dibahas dengan menggunakan penjelasan deskriptif dan dianalisa serta ditafsirkan dengan temuan bahwa kaum borjuis memperlakukan kaum proletar secara kasar dalam hal uang. Sebagai kelanjutan dari studi tersebut, artikel ini menambahkan penjelasan tentang perbuatan yang dilakukan tuan Krabs berdasarkan konsep strategi budaya popular yang mencari keuntungan dengan mengorbankan kaum proletar.Kata kunci: karya sastra popular, kartun, penindasan, Marxism